Red and blue nation? characteristics and causes of America's polarized politics - Nivola, Pietro S.; Brady, David W. (Hoover Institution on War, Revolution, and Peace, Stanford University ; Brookings Institution Press, 2006)
"Considers the extent to which polarized views among political leaders and activists are reflected in the population at large. Pays particular attention to factors such as the increased influence of religion and the changing nature of the media and offers thoughtful analyses of the underlying problems"--Provided by publisher
Keywords: Political parties -- United States.; Party affiliation -- United States.; Polarization (Social sciences); United States -- Politics and government.; Partis politiques -- Adhésion -- États-Unis.; Polarisation collective.; États-Unis -- Politique et gouvernement.; POLITICAL SCIENCE -- Political Process -- Political Parties.; POLITICAL SCIENCE -- Political Ideologies -- Conservatism & Liberalism.; Party affiliation; Political parties; Politics and government; United States